2008
DOI: 10.1021/bi800945t
|View full text |Cite
|
Sign up to set email alerts
|

Different Structural Changes Occur in Blue- and Green-Proteorhodopsins during the Primary Photoreaction

Abstract: We examine the structural changes during the primary photoreaction in blue-absorbing proteorhodopsin (BPR), a light-driven retinylidene proton pump, using low-temperature FTIR difference spectroscopy. Comparison of the light induced BPR difference spectrum recorded at 80 K to that of green-absorbing proteorhodopsin (GPR) reveals that there are several differences in the BPR and GPR primary photoreactions despite the similar structure of the retinal chromophore and all-trans → 13-cis isomerization. Strong bands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 56 publications
4
26
2
Order By: Relevance
“…The cyclicity and thermal data presented in this work, although collected in a detergent environment, further demonstrate the differences between BPR and GPR 78,79. The reduced photochemical stability of BPR best exemplifies this difference and might be viewed to support those proposals that BPR is a regulatory or sensory protein 31,70.…”
Section: Resultssupporting
confidence: 69%
“…The cyclicity and thermal data presented in this work, although collected in a detergent environment, further demonstrate the differences between BPR and GPR 78,79. The reduced photochemical stability of BPR best exemplifies this difference and might be viewed to support those proposals that BPR is a regulatory or sensory protein 31,70.…”
Section: Resultssupporting
confidence: 69%
“…These later bands might arise from the C=O stretch of the substituted Gln residue similar to assignment of Gln residues in proteorhodopsin in this region. 30 At 170 K, the magnitudes of several of the bands in this region in WT increase [(+)1748, (−)1742, (+)1724, and (−)1709 cm −1 ] and may therefore be associated with L formation at higher temperatures. The most prominent effect of the E68Q mutation at this temperature is the disappearance of the (+)1724 and (−)1709 cm −1 bands, which indicates that these bands may arise directly from the Glu68 residue.…”
Section: Resultsmentioning
confidence: 97%
“…1) showed that, like BR and all other archaeal rhodopsins studied, the initial photochemistry involved all-trans to 13-cis isomerization of the retinylidene chromophore (see for example recent FTIR studies on green and blue proteorhodopsin [30]). In agreement, resonance Raman (RRS) measurements using 785-nm near-infrared excitation revealed that the AR3 chromophore has an all-trans structure very similar to BR (manuscript in preparation, E.C.…”
Section: Primary Phototransition Of Ar3 Involves All-trans To 13-cis mentioning
confidence: 99%